The effect of profitability and corporate financial distress on auditor turnover in Indonesia - Surtikanti, Surtikanti; Saleh, Dean Subhan; Syed Yusuf, Sharifah Norzehan; Nindyas, Rayna Ratu; Anggadini, Sri Dewi; Jamaluddin, Ali (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This study aimed to determine the effect of profitability and corporate financial distress on auditor turnover in Indonesia. This study uses descriptive and verification methods with a quantitative approach. The population used in this study are 56 annual financial statements of Manufacturing Companies in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange. The results showed that profitability had a significant effect on auditor turnover. This indicates that the profitability of a developed company has substantial funds to replace a better auditor. While the company’s financial distress has no significant effect on auditor turnover, the change of auditors will ensure the company’s financial condition so that auditor changes will not be carried out when the company is in financial distress. The impact of this research is that manufacturing companies can consider this when deciding to change auditors.